Pengaruh Corporate Social Responsibility terhadap Manajemen Laba dan Kinerja Keuangan Perusahaan (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2015-2019) - Putri, Eva Erika; Andriani, Lilik (Borobudur Accounting Review, 2021)
This study aims to test empirically the effect of Corporate Social Responsibility on Profit Management and Financial Performance. The independent variable in this study is Corporate Social Responsibility, which is measured using CSRi. While the dependent variable in this study is Earnings Management and Financial Performance. The sample used in this study were manufacturing sector companies listed on the Indonesia Stock Exchange from 2015 to 2019. The number of samples in this study was 55 from 11 companies. Determination of the sample obtained by using purposive sampling. Hypothesis testing is performed using regression analysis. The results of this study indicate that Corporate Social Responsibility has a negative effect on Profit Management and Corporate Social Responsibility has a positive effect on Financial Performance (Return On Assets, Return On Equity and Return On Sales).